Pelatihan Sistem Pengendalian Internal dan SistemInformasi Akuntansi Bagi Karyawan PT. Lampung Jasa Utama Di Kota Bandar Lampung - Arie Sarjono Idris; Nety Kumalasari; Umar Bakti; Ilham Fahrudin Yahya (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2022)
The purpose of this activity is to provide an understanding of the importance of internal control and accounting information systems in a company to minimize risk and maximize employee performance, create effective and efficient management, and avoid wasting company resources and also to improve employee quality. The method of this activity is carried out using the lecture method. The targets of this Community Service (PKM) activity are employees and management of PT. Lampung Jasa Utama which was attended by 11 participants. This training activity was well organized. This employee training activity is expected to provide in-depth understanding and a positive impact on leaders, management, employees and all company management in improving quality and implementing good and correct internal controls and information systems in the company's operational activities.